Efektivitas Edukasi Cuci Tangan Pakai Sabun (CTPS) Dalam Meningkatkan Perilaku Hidup Bersih Dan Sehat Siswa SD Negeri 93 Kendari - Rahman Rahman; Lelivianti Lelivianti; Kharisma Utami Istiani; Leni Asrawati; Luna Febrina; Mirah Lestari; Iren Natasya; Lola Uhyati; Juvita Melani Indri; Jihan Jihan; Naura Zakiyah (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Handwashing with soap (HWWS) is a healthy hygiene habit that effectively prevents infections in school-aged children. Low knowledge among elementary school students about HWWS poses a health issue in school environments. This study analyzes the impact of HWWS education on elementary school students' knowledge levels. The design is a quasi-experimental one-group pretest-posttest. Conducted at one elementary school with 29 students. Education delivered through counseling, demonstration, and direct practice. Knowledge measured via questionnaire before and after. Average scores before education were 6.3, rising to 8.9 afterward. Wilcoxon test: Z = −3.859, p-value = 0.000 (p < 0.05), indicating a significant difference. This increase aligns with health promotion theory: accurate information tailored to developmental stages boosts knowledge and fosters positive health behaviors. Demonstration and practice are effective for elementary kids due to engaging, applicable learning. Conclusion: HWWS education significantly improves elementary students' knowledge, supporting early adoption of clean and healthy living habits.